Antirelapse Efficacy of Various Primaquine Regimens for Plasmodium vivax. (10th September 2014) - Rajgor, D. D.; Gogtay, N. J.; Kadam, V. S.; Kocharekar, M. M.; Parulekar, M. S.; Dalvi, S. S.; Vaidya, A. B.; Kshirsagar, N. A.
Abstract : Background . Efficacy of standard dose of primaquine (PQ) as antirelapse for P. vivax has decreased. We aimed to assess efficacy of different PQ regimens. Methods . It was an open label, randomized, controlled, parallel group, assessor blind study comparing antirelapse efficacy of 3 PQ regimens (B = 15 mg/day × 14 days, C = 30 mg/day × 7 days, and D = 30 mg/day × 14 days) with no PQ group (A) in P. vivax patients. Paired primary and recurrence samples were subjected to 3 methods: (i) month of recurrence and genotyping, (ii) by PCR-RFLP, and (iii) PCR sequencing, to differentiate relapse and reinfection. The rates of recurrence relapse and reinfection were compared. Methods were compared for concordance between them. Results . The recurrence rate was 16.39%, 8.07%, 10.07%, and 6.62% in groups A, B, C, and D, respectively P = 0.004 . The relapse rate was 6.89%, 1.55%, 4%, and 3.85% as per the month of recurrence; 8.2%, 2%, 4.58%, and 3.68% P = 0.007 as per PCR-RFLP; and 2.73%, 1.47%, 1.55%, and 1.53% as per PCR sequencing for groups A, B, C, and D, respectively. The concordance between methods was low, 45%. Conclusion . The higher recurrence rate in no PQ as compared to PQ groups documents PQ antirelapse activity. Regimens tested were safe. However, probable resistance to PQ warrants continuous monitoring and low concordance and limitations in the methods warrant caution in interpreting.